Board Gender Diversity and Firm Performance: Evidence from big companies in China - XIE, Yi (2022)
The study examined the relationship between board gender diversity and firm performance, and the board gender diversity include female directors’ number and attributes. This study collects the panel data of big companies in China from 2015 to 2019 (5 years), measures firm performance using ROA based on accounting method and Tobin's Q based on market method, and applies regression analysis to demonstrate that board gender diversity is inconsistent with the financial and market performance of firms. The results of this dissertation show that female directors’ number has no relationship with ROA, but positively correlated with Tobin's Q, which also verifies the critical mass theory that, when the boardroom has two female directors, it will positively influence firm performance. The education level of female directors has no relationship with ROA but has negative relationship with Tobin’s Q. Female directors’ independence and leadership positively affect firm performance, with leadership having a greater influence than independence. This study provides new perspectives on the appointment of boardrooms and the establishment of fixed quotas for female directors of firms in China and around the world.